Inland : poems - Alexander, Pamela, 1948- (Iowa City : University of Iowa Press, 1997)
Pamela Alexander's poetry is characterized by inventive language, scrupulous accuracy of imagery, and a winning fusion of the comic and the deeply serious. Her subjects vary as widely as her settings, which range from the New Hampshire woods to the Arizona desert. A family life eccentric to the point of chaos, close observations of wildlife, and coastal sailing are among the poet's topics.
Down on the farm -- Impromptu -- Spectacle island, Boston Harbor -- Mt. Auburn owl -- Jugglebirds abroad -- Seminar -- From the book of foxes -- My mother and the myriad things -- Soon -- Manners -- My brother's back -- Nots -- Accidentals -- Fogbow -- Souvenir -- Mt. Pinatubo -- Fortune -- Look here -- Northeast suite -- Origin -- Passage with owls -- Slip -- Ease -- Spill -- Bog at black pond -- Understory -- The rode -- Lettered olives -- Sonoran -- The comma a portrait -- Waking -- In the house you built -- Foxlight -- Swallowing the anchor -- House song -- What we need.
Print version record.
"Winner of the Iowa poetry prize"
eBooks on EBSCOhost
Keywords: American poetry -- 20th century; Poésie américaine -- 20e siècle.; POETRY -- American -- General; American poetry; 1900-1999